2016
DOI: 10.1038/srep31496
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral Tin Dioxide Nanocrystals Anchored on Vertically Aligned Carbon Aerogels as High Capacity Anode Materials for Lithium-Ion Batteries

Abstract: A novel binder-free graphene - carbon nanotubes - SnO2 (GCNT-SnO2) aerogel with vertically aligned pores was prepared via a simple and efficient directional freezing method. SnO2 octahedrons exposed of {221} high energy facets were uniformly distributed and tightly anchored on multidimensional graphene/carbon nanotube (GCNT) composites. Vertically aligned pores can effectively prevent the emersion of “closed” pores which cannot load the active SnO2 nanoparticles, further ensure quick immersion of electrolyte t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…It is observed that Cu–Sn–O x /rGO exhibits 42.6% O-vacancies, whereas SnO 2 /rGO demonstrates 33.8% O-vacancies. The high-resolution XPS spectrum of Sn 3d orbitals in Figure d displays two distinct peaks at 495.7 and 487.3 eV, which can be attributed to the 3d 3/2 and 3d 5/2 peaks in the binding energy between Sn 4+ and O. , The disparity in binding energy between the two peaks is 8.4 eV, which aligns with the comparison between the 3d 3/2 and 3d 5/2 peaks of Sn 4+ in SnO 2 . It has been observed that the binding energies of the Sn 3d 5/2 and 3d 3/2 peaks shift from 495.7 and 487.3 eV in SnO 2 /rGO to 495.1 and 487.0 eV in Cu–Sn–O x /rGO. This shift is due to the differing electronegativities of Cu (1.90) and Sn (1.96), leading to a greater transfer of electrons from Cu 2+ to Sn 4+ in Cu–Sn–O x /rGO.…”
Section: Results and Discussionsupporting
confidence: 69%
“…It is observed that Cu–Sn–O x /rGO exhibits 42.6% O-vacancies, whereas SnO 2 /rGO demonstrates 33.8% O-vacancies. The high-resolution XPS spectrum of Sn 3d orbitals in Figure d displays two distinct peaks at 495.7 and 487.3 eV, which can be attributed to the 3d 3/2 and 3d 5/2 peaks in the binding energy between Sn 4+ and O. , The disparity in binding energy between the two peaks is 8.4 eV, which aligns with the comparison between the 3d 3/2 and 3d 5/2 peaks of Sn 4+ in SnO 2 . It has been observed that the binding energies of the Sn 3d 5/2 and 3d 3/2 peaks shift from 495.7 and 487.3 eV in SnO 2 /rGO to 495.1 and 487.0 eV in Cu–Sn–O x /rGO. This shift is due to the differing electronegativities of Cu (1.90) and Sn (1.96), leading to a greater transfer of electrons from Cu 2+ to Sn 4+ in Cu–Sn–O x /rGO.…”
Section: Results and Discussionsupporting
confidence: 69%
“…Two distinct peaks at 0.7 and 0.2 V appear during the initial cycle but vanish in the following cycles, which is normally the result of solid electrolyte interphase (SEI) film formation, the reduction of SnO x to metallic Sn, and partial irreversibility of lithium oxide. ,, In the subsequent cycles, the well-defined cathodic peaks at 0.27 and 0.56 V are related to lithium alloying with Sn. The distinct anodic peaks at 0.67, 0.75, and 0.82 V correspond to the delithiation process of Li x Sn. ,, The anodic peaks at 1.23 and 1.88 V are attributed to the partially reversible reaction of Sn to SnO 2 . , The entire process is described by eqs and . Near 2.95 V, an intense peak occurs in the CV curves of the first oxidation cycle, which might be on account of the side reactions between the electrolyte and the surface of the amorphous carbon .…”
Section: Resultsmentioning
confidence: 99%
“…24,43,44 The anodic peaks at 1.23 and 1.88 V are attributed to the partially reversible reaction of Sn to SnO 2 . 45,46 The entire process is described by eqs 2 and 3. Near 2.95 V, an intense peak occurs in the CV curves of the first oxidation cycle, which might be on account of the side reactions between the electrolyte and the surface of the amorphous carbon.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, stannic oxides present a good chemical stability with high melting and boiling points with low production costs. These can be applied as gas sensors, humidity sensors, and transparent electrodes for solar cells, varistors, optoelectronic devices, capacitors, flat-panel displays, high capacity anodes in lithium-ion batteries, and many other electronic device applications [1][2][3].…”
Section: Introductionmentioning
confidence: 99%